Redesigning Indonesia’s Energy Governance: A Progressive Asymmetric Decentralization Framework for an Accelerated Energy Transition - Novemyanto, Alfin Dwi (UIN Sunan Gunung Djati Bandung, 2025)
The urgency of accelerating energy transition in Indonesia arises from its commitment to the Paris Agreement and the national target of achieving Net Zero Emissions by 2060. However, the current legal framework remains highly centralized, limiting the autonomy of local governments and constraining innovation in renewable energy development. This study aims to propose a progressive legal framework through an asymmetric decentralization model that provides differentiated authority for regions based on their renewable energy potential and climate risk exposure. The research employs normative legal methods with a statute approach, conceptual analysis based on the welfare state theory and subsidiarity principle, and a comparative study with India and South Africa, which have implemented more decentralized models of energy governance. Findings show that Indonesia’s legal system suffers from normative deficits, particularly in integrating justice, participation, and flexibility into energy governance. The proposed asymmetric decentralization model emphasizes granting special authority to regions with strategic roles in the energy transition, supported by a green fiscal transfer mechanism and multilevel governance structures. This model strengthens Indonesia’s ability to bridge international climate commitments with local socio-ecological realities. The study concludes that reconstructing Indonesia’s energy law through asymmetric decentralization offers both academic novelty and practical relevance, providing a path toward more equitable, participatory, and adaptive energy governance. The contribution of this research lies in its formulation of a context-sensitive legal model that advances interdisciplinary debates on law, energy transition, and sustainable development in the Global South.